Rickets in a 4-year-old child with lamellar ichthyosis. - Litaiem, N.; Jones, M.; El Khalifa, J.; Fazaa, B. (European Journal of Pediatric Dermatology, 2013)
A 4-year-old child presented with generalized hyperkeratosis and bone deformity. On the basis of the clinical and biochemical findings, he was diagnosed as a case of lamellar ichthyosis with rickets. He was treated with vitamin D3 and calcium supplements. Nutritional rickets has been reported in children with various types of ichthyosis like lamellar and X-linked types. We report this case of lamellar ichthyosis with rickets for its rarity.